2008
DOI: 10.1111/j.1464-5491.2008.02492.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Educator talk’ and patient change: some insights from the DESMOND (Diabetes Education and Self Management for Ongoing and Newly Diagnosed) randomized controlled trial

Abstract: Results: Where data from the event coding indicated educators were talking less and meeting targets for being less didactic, a greater change in reported illness beliefs of participants was seen. However, educators struggled to meet targets for most sessions of the programme.Conclusion: The amount of time educators talk in a self-management programme may provide a practical marker for the effectiveness of the education process, with less educator talk denoting a more facilitative/ less didactic approach. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 14 publications
0
52
0
Order By: Relevance
“…The program is 180 min long; 105 min are dedicated to addressing the causes, complications, timeline, and identity of IGT and 75 min are targeted to addressing the perceived effectiveness of exercise as a treatment for IGT, walking self-efficacy beliefs, barriers to walking, and self-regulatory strategies. The program has a written curriculum, modeled on the person-centered philosophy and learning techniques developed for the Diabetes Education and Self-Management for Ongoing and Newly Diagnosed (DESMOND) program (911), an established nationally available 6-h structured educational program designed to promote lifestyle change and self-management for those with newly diagnosed type 2 diabetes in the U.K.…”
Section: Methodsmentioning
confidence: 99%
“…The program is 180 min long; 105 min are dedicated to addressing the causes, complications, timeline, and identity of IGT and 75 min are targeted to addressing the perceived effectiveness of exercise as a treatment for IGT, walking self-efficacy beliefs, barriers to walking, and self-regulatory strategies. The program has a written curriculum, modeled on the person-centered philosophy and learning techniques developed for the Diabetes Education and Self-Management for Ongoing and Newly Diagnosed (DESMOND) program (911), an established nationally available 6-h structured educational program designed to promote lifestyle change and self-management for those with newly diagnosed type 2 diabetes in the U.K.…”
Section: Methodsmentioning
confidence: 99%
“…Also, providing more information was not always regarded as being a better approach. Skinner et al (2008) for example reported that the more the patients' knowledge of their illness increased the less the educators talked. Dibbelt et al (2010) described that although physicians showed good capabilities to establish emotional relationships during their study they still lacked the ability to effectively inform and motivate their patients.…”
Section: Information Provisionmentioning
confidence: 99%
“…The 10-second event coding is an objective measure and an established method of measuring talk time-to-educator ratio. 258,259 DOI: 10.3310/pgfar05110 PROGRAMME GRANTS FOR APPLIED RESEARCH 2017 VOL. 5 NO.…”
mentioning
confidence: 99%